Comparison of some kinetic properties of pyruvate kinase in liver tissue of normal and diabetic rats - Yilmaz, S (Scientific Technical Research Council Turkey, 2003)
Diabetes mellitus was induced in Wistar-Albino type male rats with a single dose of streptozotocin (60 mg/kg intraperitoneally). The kinetic properties of pyruvate kinase were investigated in normal and diabetic rat liver tissue. In normal rat liver tissue. the incubation period of pyruvate kinase was 15 min and the optimum pH was 8. In diabetic rat liver tissue, the incubation period of pyruvate kinase was 10 min and the optimum pH was 7. Activation was found in normal and diabetic rat liver tissues with magnesium chloride and potassium chloride. Phospho(enol)pyruvate is an enzyme substrate; in the absence of the fructose-1,6-diphosphate its graphic showed a sigmoidal plot, and in the presence of the fructose-1,6-diphosphate its graphic turned into a hyperbolic plot of Michaelis-Menten kinetics. Different Km pyruvate kinase values for phospho(enol)pyruvate were found in normal and diabetic liver tissues, and the Km value of fructose-1,6-diphosphate was determined as low. A low phospho(enol)pyruvate enzyme affinity was identified in diabetic liver tissue.
Normal ve diabetik rat karaci?er dokusunda pirüvat kinazin bazi kinetik özelliklerinin karşilaştirilmasi
Keywords: diabetes; liver tissue; pyruvate kinase; kinetic properties